Educational booklet for elders with type 2 diabetes mellitus - George, Nenmanikkara Geoviya; Moosabba, M. S.; Sivakumar, M. R.; Suvarna, Manjula (International Journal Of Community Medicine And Public Health, 2021)
Background: Consistently following and practicing the instructions given in the educational booklets helps in the disease awareness and its management. Methods: The study was developed by formulating the booklet content; content selection and source reference; framing the content; artfully crafting the pictures; booklet layout; approval by the specialist and audience; modifying and proofreading. For content validation, the item-level content validity index (I-CVI) score and scale level content validity index (S-CVI) score of minimum 0.80 was considered. Results: The booklet was created by focusing on 5 main aspects namely information about the disease and the importance about the lifestyle changes, exercises, advices that needs to be considered while exercising, footcare and fall prevention techniques. The recommendations made by the experts and the participants were accepted and incorporated in the booklet. The mean I-CVI and S-CVI scores are >0.90. The booklet was easy to read, understand and apply by the experts and participants. Conclusions: The results indicated that validated booklet can be considered as a useful educational tool for promoting the wellness among the elders with type 2 diabetes mellitus.